Gene Expression Profile Induced by Two Different Variants of Street Rabies Virus in Mice - Appolinário, Camila M. [UNESP]; Daly, Janet M.; Emes, Richard D.; Marchi, Fabio Albuquerque; Ribeiro, Bruna Leticia Devidé [UNESP]; Megid, Jane [UNESP] (MDPI, 2022)
Pathogenicity and pathology of rabies virus (RABV) varies according to the variant, but the mechanisms are not completely known. In this study, gene expression profile in brains of mice experimentally infected with RABV isolated from a human case of dog rabies (V2) or vampire bat-acquired rabies (V3) were analyzed. In total, 138 array probes associated with 120 genes were expressed differentially between mice inoculated with V2 and sham-inoculated control mice at day 10 post-inoculation. A single probe corresponding to an unannotated gene was identified in V3 versus control mice. Gene ontology (GO) analysis revealed that all of the genes upregulated in mice inoculated with V2 RABV were involved in the biological process of immune defense against pathogens. Although both variants are considered pathogenic, inoculation by the same conditions generated different gene expression results, which is likely due to differences in pathogenesis between the dog and bat RABV variants. This study demonstrated the global gene expression in experimental infection due to V3 wild-type RABV, from the vampire bat Desmodus rotundus, an important source of infection for humans, domestic animals and wildlife in Latin America.
Keywords: dog; mice; microarray analysis; pathogenesis; rabies virus; vampire bat